Role of 3 Tesla Magnetic Resonance Imaging for Shoulder Pain and Instability in Tertiary Care Centre - J. Nanda Gopal; A. Sravan Krishna Reddy; Harathi Surla; P. Suneetha (Asian Journal of Medical Radiological Research, 2022)
Background: The objective of our study is to demonstrate the role of 3Tesla MRI in detecting shoulder pathologies encountered in patients with shoulder pain. Subjects and Methods: It is a hospital based prospective observational study which was carried out in 50 patients with a history of shoulder pain and suspects of rotator cuff tear and glenoid labral injuries in Narayana medical college and general hospital, Nellore. All age group patients were included in the study without any gender predilection. Results: Out of the 50 patients, 5 patients were excluded. Among the 45 patients included in the study the various pathologies were detected on MRI. Conclusion: To understand the role of MRI in the diagnosis of shoulder pain and instability and to understand pitfalls. MRI is the best among various imaging modalities as it is non-invasive and provides a better depiction of the soft tissues of the shoulder joint. It has the added advantage of being nonionizing modality.